Computation of exact diffraction field from its distributed samples - ESMER, GÖKHAN BORA (SPIE-INT SOC OPTICAL ENGINEERING, 2017)
Calculation of the exact diffraction field of a three dimensional object from its samples taken over the entire space can be obtained by defining it as an inverse problem. For that purpose, we propose an algorithm based on L-1-norm minimization to solve the defined inverse problem. Proposed algorithm paves the way to reconstruct the original diffraction field by having less number of samples compared to the methods based on L-2-norm minimization.
Keywords: Diffraction Field Calculation; L-1-norm minimization; L-2-norm minimization; Inverse Problem; CURVED SURFACES